COMPUTER RENTAL SYSTEM ADMINISTRATION IN PT.NUGRA SENTANA USING MICROSOFT VISUAL BASIC 6.0 - Rifni Rifni; Yuce Yuliani,SKom, MM Yuce Yuliani,SKom, MM (Jurnal Sistem Informasi, 2003)
Processing large amounts of data with the manual method requires more time andaccuracy, a program created in this paper tries to offer data processing moreeffectively and efficiently. With computerized data processing more quickly,accurately and efficiently and the process of computerization can work well whensupported by proper processing and well structured so that it can minimize mistakesand neatness can be sustained.